2022
DOI: 10.1038/s41419-022-04674-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomic and metabolomic characterization of COVID-19 survivors 6 months after discharge

Abstract: Coronavirus disease 2019 (COVID-19) has gained prominence as a global pandemic. Studies have suggested that systemic alterations persist in a considerable proportion of COVID-19 patients after hospital discharge. We used proteomic and metabolomic approaches to analyze plasma samples obtained from 30 healthy subjects and 54 COVID-19 survivors 6 months after discharge from the hospital, including 30 non-severe and 24 severe patients. Through this analysis, we identified 1019 proteins and 1091 metabolites. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 82 publications
6
29
0
Order By: Relevance
“…COVID-19 infection causes immune response dysregulation, and the continuous abnormalities in LCFA and lipid metabolism showed a long-term immune response problem. The findings are similar to those of COVID-19 survivors 6 months after discharge (Li et al, 2022), indicated that the metabolic disturbance of lipid is associated with the long-term chronic discomfort of COVID-19 healers.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…COVID-19 infection causes immune response dysregulation, and the continuous abnormalities in LCFA and lipid metabolism showed a long-term immune response problem. The findings are similar to those of COVID-19 survivors 6 months after discharge (Li et al, 2022), indicated that the metabolic disturbance of lipid is associated with the long-term chronic discomfort of COVID-19 healers.…”
Section: Discussionsupporting
confidence: 77%
“…As a result, little is known about the metabolic status of COVID-19 patients in the late stages of infection. A recent proteomic and metabolomic study revealed that COIVD-19 caused persistent abnormalities after discharge ( Li et al, 2022 ), emphasizing the importance of a study focused on cured COIVD-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…MHFAs are active anti-inflammatory and pro-resolution mediators ( Serhan et al, 2008 ), two and five of MHFA species were respectively reduced in young and elder discharged patients, whose reduction demonstrates a potential deficit in the resolve of inflammatory in survivors of non-severe COVID-19. Li et al (2022) also found that two MHFA species were downregulated in plasma of severe and non-severe COVID-19 survivors 6 months after discharge from the hospital.…”
Section: Resultsmentioning
confidence: 78%
“…It was closely associated with fatigue or muscle weakness syndrome of the COVID-19 survivors in our cohort. The accumulation of TG was also found in the plasma of COVID-19 survivors after discharge ( Xu et al, 2021 ; Li et al, 2022 ). Besides, elevated TG and reduced HDL-c might increase the risk of coronary heart diseases in elder survivors ( Krauss and Siri, 2004 ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation